The triangular prism has a volume of
.. V = Bh = (1/2)*(4ft *8 ft)*(24 ft) = 384 ft^3
Answer:
c.
Step-by-step explanation:
Hello!
To take a sample to estimate the mean height of all students at a university and that the value you reach is statistically valid you need the sampling method to be random and representative of the whole population, in this example, all university students.
a. Measure the heights of 50 students found in the gym during basketball intramurals.
This method is not the best because you would be sampling only basketball players leaving all other students of the university outside, i.e. your sample will not be representative of all the students, just the ones that play basketball.
b. Measure the heights of all engineering majors.
This method is not good, the sample only represents engineering mayors meaning that it does not include the students of any other subjects.
c. Measure the heights of the students selected by choosing the first name on each page of the campus phone book.
With this method you choose students regardless of the sport or major they're are taking, it is more representative of the population of university students, of the three options, this is the best one.
I hope it helps!
35 percent got eaten.
To solve: you’d take the number of flowers eaten, 7. And you’d divide it by the overall number, 20. Then you’d get 0.35, which would be your percent.
Answer:
a) So, this integral is convergent.
b) So, this integral is divergent.
c) So, this integral is divergent.
Step-by-step explanation:
We calculate the next integrals:
a)
![\int_1^{\infty} e^{-2x} dx=\left[-\frac{e^{-2x}}{2}\right]_1^{\infty}\\\\\int_1^{\infty} e^{-2x} dx=-\frac{e^{-\infty}}{2}+\frac{e^{-2}}{2}\\\\\int_1^{\infty} e^{-2x} dx=\frac{e^{-2}}{2}\\](https://tex.z-dn.net/?f=%5Cint_1%5E%7B%5Cinfty%7D%20e%5E%7B-2x%7D%20dx%3D%5Cleft%5B-%5Cfrac%7Be%5E%7B-2x%7D%7D%7B2%7D%5Cright%5D_1%5E%7B%5Cinfty%7D%5C%5C%5C%5C%5Cint_1%5E%7B%5Cinfty%7D%20e%5E%7B-2x%7D%20dx%3D-%5Cfrac%7Be%5E%7B-%5Cinfty%7D%7D%7B2%7D%2B%5Cfrac%7Be%5E%7B-2%7D%7D%7B2%7D%5C%5C%5C%5C%5Cint_1%5E%7B%5Cinfty%7D%20e%5E%7B-2x%7D%20dx%3D%5Cfrac%7Be%5E%7B-2%7D%7D%7B2%7D%5C%5C)
So, this integral is convergent.
b)
![\int_1^{2}\frac{dz}{(z-1)^2}=\left[-\frac{1}{z-1}\right]_1^2\\\\\int_1^{2}\frac{dz}{(z-1)^2}=-\frac{1}{1-1}+\frac{1}{2-1}\\\\\int_1^{2}\frac{dz}{(z-1)^2}=-\infty\\](https://tex.z-dn.net/?f=%5Cint_1%5E%7B2%7D%5Cfrac%7Bdz%7D%7B%28z-1%29%5E2%7D%3D%5Cleft%5B-%5Cfrac%7B1%7D%7Bz-1%7D%5Cright%5D_1%5E2%5C%5C%5C%5C%5Cint_1%5E%7B2%7D%5Cfrac%7Bdz%7D%7B%28z-1%29%5E2%7D%3D-%5Cfrac%7B1%7D%7B1-1%7D%2B%5Cfrac%7B1%7D%7B2-1%7D%5C%5C%5C%5C%5Cint_1%5E%7B2%7D%5Cfrac%7Bdz%7D%7B%28z-1%29%5E2%7D%3D-%5Cinfty%5C%5C)
So, this integral is divergent.
c)
![\int_1^{\infty} \frac{dx}{\sqrt{x}}=\left[2\sqrt{x}\right]_1^{\infty}\\\\\int_1^{\infty} \frac{dx}{\sqrt{x}}=2\sqrt{\infty}-2\sqrt{1}\\\\\int_1^{\infty} \frac{dx}{\sqrt{x}}=\infty\\](https://tex.z-dn.net/?f=%5Cint_1%5E%7B%5Cinfty%7D%20%5Cfrac%7Bdx%7D%7B%5Csqrt%7Bx%7D%7D%3D%5Cleft%5B2%5Csqrt%7Bx%7D%5Cright%5D_1%5E%7B%5Cinfty%7D%5C%5C%5C%5C%5Cint_1%5E%7B%5Cinfty%7D%20%5Cfrac%7Bdx%7D%7B%5Csqrt%7Bx%7D%7D%3D2%5Csqrt%7B%5Cinfty%7D-2%5Csqrt%7B1%7D%5C%5C%5C%5C%5Cint_1%5E%7B%5Cinfty%7D%20%5Cfrac%7Bdx%7D%7B%5Csqrt%7Bx%7D%7D%3D%5Cinfty%5C%5C)
So, this integral is divergent.
Answer 1:
It is given that the positive 2 digit number is 'x' with tens digit 't' and units digit 'u'.
So the two digit number x is expressed as,
![x=(10 \times t)+(1 \times u)](https://tex.z-dn.net/?f=x%3D%2810%20%5Ctimes%20t%29%2B%281%20%5Ctimes%20u%29)
![x=10t+u](https://tex.z-dn.net/?f=x%3D10t%2Bu)
The two digit number 'y' is obtained by reversing the digits of x.
So, ![y=(10 \times u)+(1 \times t)](https://tex.z-dn.net/?f=y%3D%2810%20%5Ctimes%20u%29%2B%281%20%5Ctimes%20t%29)
![y=10u+t](https://tex.z-dn.net/?f=y%3D10u%2Bt)
Now, the value of x-y is expressed as:
![x-y=(10t+u)-(10u+t)](https://tex.z-dn.net/?f=x-y%3D%2810t%2Bu%29-%2810u%2Bt%29)
![x-y=10t+u-10u-t](https://tex.z-dn.net/?f=x-y%3D10t%2Bu-10u-t)
![x-y=9t-9u](https://tex.z-dn.net/?f=x-y%3D9t-9u)
![x-y=9(t-u)](https://tex.z-dn.net/?f=x-y%3D9%28t-u%29)
So,
is equivalent to (x-y).
Answer 2:
It is given that the sum of infinite geometric series with first term 'a' and common ratio r<1 = ![\frac{a}{1-r}](https://tex.z-dn.net/?f=%5Cfrac%7Ba%7D%7B1-r%7D)
Since, the sum of the given infinite geometric series = 200
Therefore,![\frac{a}{1-r}=200](https://tex.z-dn.net/?f=%5Cfrac%7Ba%7D%7B1-r%7D%3D200)
Since, r=0.15 (given)
![\frac{a}{1-0.15}=200](https://tex.z-dn.net/?f=%5Cfrac%7Ba%7D%7B1-0.15%7D%3D200)
![\frac{a}{0.85}=200](https://tex.z-dn.net/?f=%5Cfrac%7Ba%7D%7B0.85%7D%3D200)
![a=0.85 \times 200](https://tex.z-dn.net/?f=a%3D0.85%20%5Ctimes%20200)
a=170
The nth term of geometric series is given by
.
So, second term of the series =
= ar
Second term = ![170 \times 0.15](https://tex.z-dn.net/?f=170%20%5Ctimes%200.15)
= 25.5
So, the second term of the geometric series is 25.5
Step-by-step explanation: